Magnetic resonance imaging reveals elevated aortic pulse wave velocity in obese and overweight adolescents. Issue 6 (23rd August 2017) - Caterini, J. E.; Banks, L.; Wells, G. D.; Cifra, B.; Slorach, C.; McCrindle, B. W.; Seed, M.
Summary: The aortic pulse wave velocity (PWV) measured via cardiac magnetic resonance (CMR) can be used to non‐invasively assess changes in arterial stiffness and potential underlying vascular dysfunction. This technique could unmask early arterial dysfunction in overweight and obese youth at risk for cardiovascular disease. We sought to determine the association between vascular stiffness, percentage body fat, body mass index (BMI), and cardiac function in adolescents across the weight spectrum through both CMR and standard applanation tonometry (AT)‐based PWV measurements. PWV and left‐ventricular cardiac function were assessed using 3.0 T CMR in obese and overweight (OB/OW) participants ( n = 12) and controls ( n = 7). PWV was also estimated via carotid–femoral AT. OB/OW participants did not differ from healthy‐weight controls regarding cardiometabolic risk factors or physical activity levels, but there was a trend towards higher levels of triglycerides in obese/overweight participants ( P = 0.07). Mean PWV was higher in obese participants when corrected for age and sex ( P = 0.01), and was positively associated with BMI ( β = 0.51, P = 0.02). PWV estimated through AT was not significantly different between groups. Cardiac function measured by left‐ventricular ejection fraction z ‐score was inversely associated with mean PWV ( β = −0.57, P = 0.026). Increasing arterial stiffness and decreasing cardiac function were evident among our overweight and obese cohort. PWV estimated by CMR could detect early increases in arterial stiffness vs. traditional AT measurements of PWV.